Functional Analysis Diagrams in Science and Technology Education - Ioannis Michalakoudis; Pavlos Dimitriou; Apollon Koutlidis; Peter Childs (MDPI AG, 2023)
With the world currently facing an escalating environmental crisis and major virus disease outbreaks, the need to significantly grow the STEM workforce ranks has never been more urgent. The authors propose a novel teaching methodology involving functional analysis diagrams (FADs) as an educational aid. The paper presents a method to quantitatively assess the effects of the proposed intervention in an educational setting alongside a pilot study conducted in a South Korean secondary school with non-native English-speaking students (n = 39). The written assessment results indicate that the FAD-assisted method can have a measurable effect and have the potential to assist students with lower scores in English. This pilot study's results suggest that FAD models of engineering systems can enhance knowledge transfers in technology and engineering education. Experimental validation using the proposed method was shown to be feasible and would require a moderate-sized sample (n ≥ 168) for a future full-scale study.